Olea europaea Leaves and Human Health: From Basic Research to Clinical Applications - Limam, Inès; Abdelkarim, Mohamed (Biomedicine & Healthcare Research, 2026)
Olive leaves (Olea europaea L.), once considered an agricultural by-product, are now recognized as a valuable source of bioactive polyphenols—mainly oleuropein and hydroxytyrosol—with high biomedical potential. Extensive experimental evidence demonstrates their strong antioxidant, anti-inflammatory, cardiometabolic, neuroprotective, and anticancer properties. These effects are mediated through key molecular pathways involved in oxidative stress regulation, inflammation control, apoptosis induction, and inhibition of tumor proliferation and angiogenesis. Notably, olive leaf compounds exhibit selective cytotoxicity toward cancer cells while preserving normal cell viability, supporting their potential role in integrative oncology. Although clinical investigations still limited in number, available trials have reported significant improvements in blood pressure, lipid metabolism, glucose tolerance, and cognitive performance, with a generally good safety profile in the available trials. Beyond their pharmacological promise, olive leaves offer an environmentally sustainable avenue for the valorization of olive cultivation by-products, aligning human health benefits with circular economy principles. This narrative review synthesizes mechanistic and clinical findings, while also discussing current limitations such as extract variability and the need for further clinical validation.